Исследование товарных продуктов Томской нефти - Страмковская К. К.; Смольянинова Н. М.; Смольянинов С. И. Станислав Иванович; Белоусов А. Н.; Шуливейстров А. Е. (1974, 1974)
Заглавие с титульного листа